Targeted Killing of Staphylococcus aureus Using Specific Peptides Displayed on Yeast Vacuoles - Jaewoong Lee; Ngoc-Tu Nguyen; Le-Minh Tran; Yang-Hoon Kim; Jiho Min (Microbiology Spectrum, 2023)
ABSTRACT Staphylococcus aureus is a common pathogen that causes health care-related and community-associated infections. In this study, we provide a novel system that can recognize and kill S. aureus bacteria. The system is specifically based on a combination of the phage display library technique and yeast vacuoles. A phage clone displaying a peptide capable of specific binding to a whole S. aureus cell was selected from a 12-mer phage peptide library. The peptide sequence was SVPLNSWSIFPR. The selected phage’s ability to bind specifically with S. aureus was confirmed using an enzyme-linked immunosorbent assay, and the chosen peptide was then synthesized. The results showed that the synthesized peptides displayed high affinity with S. aureus but low binding ability with other strains, including Gram-negative and Gram-positive bacteria such as Salmonella sp., Shigella spp., Escherichia coli, and Corynebacterium glutamicum. In addition, yeast vacuoles were used as a drug carrier by encapsulating daptomycin, a lipopeptide antibiotic used to treat Gram-positive bacterial infections. The expression of specific peptides at the encapsulated vacuole membrane created an efficient system that can specifically recognize and kill S. aureus bacteria. IMPORTANCE The phage display method was used to select peptides with high affinity and specificity for S. aureus, and these peptides were then induced to be expressed on the surface of yeast vacuoles. These surface-modified vacuoles can act as drug carriers, with drugs such as the lipopeptide antibiotic daptomycin loaded inside. An advantage of using yeast vacuoles as a drug carrier is that they can be easily produced through yeast culture, making the approach cost-effective and suitable for large-scale production and potential implementation in clinical settings. This novel approach offers a promising way to specifically target and eliminate S. aureus that could ultimately lead to improved treatment of bacterial infections and reduced risk of antibiotic resistance.